Evaluating Healthcare Performance in Low- and Middle-Income Countries: A Pilot Study on Selected Settings in Ethiopia, Tanzania, and Uganda - Paolo Belardi; Ilaria Corazza; Manila Bonciani; Fabio Manenti; Milena Vainieri (MDPI AG, 2022)
The literature reports some experiences regarding the design of integrated healthcare Performance Evaluation Systems (PES) applied in Low- and Middle-income Countries (LMIC). This study describes the design of an integrated and bottom-up PES aimed at evaluating healthcare services delivery in rural settings. The analysis involved four hospitals and their relative health districts in Ethiopia, Tanzania, and Uganda. The evaluation process was undertaken for those indicators that could be evaluated using the same reference standard. The evaluation scores were determined through the international standards identified in the literature or through benchmarking assessment. Both administrative and health data were extracted from the hospitals’ registers and District Health Information Systems (DHIS) from 2017 to 2020. We defined 128 indicators: 88 were calculated at the hospital level and 40 at the health district level. The evaluation process was undertaken for 48 indicators. The evaluated indicators are represented using effective graphical tools. In settings characterised by multiple healthcare providers, this framework may contribute to achieving good governance through performance evaluation, benchmarking, and accountability. It may promote evidence-based decision-making in the planning and allocation of resources, thus ultimately fostering quality improvement processes and practices, both at the hospital and health district level.
Keywords: Performance evaluation system, multidimensional performance evaluation, constructivist approach, health system, healthcare, international benchmarking